University e-learning methodologies and their financial implications: evidence from Uganda - Eton, Marus; Rest, Chance (Emerald Publishing Limited, 2022)
Purpose – This paper aims to analyze the financial implications associated with Ugandan universities employing e-learning techniques and to suggest sound policy solutions to the problems the investigation found. Design/methodology/approach – To illustrate how e-learning is used in Uganda, the study used a descriptive research design. The study used a quantitative methodology to highlight the various experiences associated with utilizing e-learning platforms from various universities. A questionnaire survey was distributed to university students, and the data were analyzed using descriptive statistics in order to understand the usage of e-learning and Persons correlation to understand the degree of the relationship between the study variables. Findings – The study findings reveal that e-learning approaches in universities are favorably correlated with their financial implications (r 5 0.598; p-value 0.05). It was excruciatingly difficult to access online learning resources and platforms, and there was a severe lack of power. Some academic staff members lacked adequate e-learning platform training, and students noted that e-learning eased communication between students and lecturers, whereas Internet subscription and acquisition of mobile devices were expensive. Research limitations/implications – The research was limited to three districts in western Uganda, and thus, it may not be possible to extrapolate the results to the entire nation. Practical implications – Universities are open to these changes since the digital world is moving more quickly, overall, and this trend has crept into education as well. Policymakers and other universities may utilize the study’s findings to inform their decisions. Originality/value – The study offers useful insights into how e-learning systems have altered university teaching methods.